Increasing Productivity Through Microbiome Control In Cultivation Of Mushrooms (Agaricus Bisporus): Metagenomic And Biotechnological Approaches (Open Academia: Journal of Scholarly Research, 2026)
This study explores the possibilities of increasing yield in the cultivation of Agaricus bisporus mushrooms through the management of the compost microbiome. Using metagenomic and biotechnological approaches, beneficial bacteria such as Bacillus and Pseudomonas can improve substrate quality, accelerate mycelial growth, and enhance yield by 15–30%. Furthermore, microbiome management plays an important role in reducing diseases and obtaining environmentally friendly products. Additionally, during the compost preparation process, managing the microbiome can improve substrate quality, reduce diseases, and enable the production of eco-friendly products.